"An age semi-pathological”: Adolescence and sex education in the second and the third decade of the twenty century in Colombia (Encuentros, 2022)
Between the second and the third decade of the twenty century in Colombia, emerged in a variety of discourses (medical, hygienically, and pedagogical) some subjects about adolescence, the particularities of this stage, and the challenges for its training. In particular, it was identified that adolescence like a sexual age what implies truly changes for who whose living it, and risks for society and even for themselves. In this article We analyses some discourses of intellectuals and academics of the period (pedagogues, doctors, hygienists, lawyers), identifying the use, circulation and assimilation of the notion of adolescence, as well as the regularities and associations with other discourses contextually situated around to the emergence of new and significant forms of government of the population.
Keywords: Keywords: Adolescence; sexual differences, sex education; government modes.